2016
DOI: 10.1016/j.ejogrb.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal cuff closure technique and the risk for infected pelvic hematoma after vaginal hysterectomy

Abstract: A significant reduction in the incidence of infected pelvic hematoma following vaginal hysterectomy was noted using a surgical technique that allows for drainage of blood and debris through the vaginal cuff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…19 A significant reduction in the incidence of infected pelvic hematoma following vaginal hysterectomy was noted using an open surgical technique that allows for drainage of blood and debris through the vaginal cuff (3.8% vs. 13.5%, p<0.0001). 20…”
Section: Resultsmentioning
confidence: 99%
“…19 A significant reduction in the incidence of infected pelvic hematoma following vaginal hysterectomy was noted using an open surgical technique that allows for drainage of blood and debris through the vaginal cuff (3.8% vs. 13.5%, p<0.0001). 20…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a retrospective study found that leaving a patent tract in the vaginal vault instead of a complete closure significantly reduced the possibility of pelvic hematoma infection after a vaginal hysterectomy. They suggested that inserting a vault drain significantly reduced the incidence of infected pelvic hematomas compared to the complete closure of the vaginal vault [ 11 ].…”
Section: Discussionmentioning
confidence: 99%